Aransemen Ansambel Woodwind Sebagai Identitas Orkes Keroncong Gita Puspita di Tegal - Meizan Riza Arhamni; Abdul Rachman (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2021)
The Keroncong Orchestra Gita Puspita Orchestra is one of the Keroncong Orchestras that has a place in the hearts of the people of Tegal Regency. This happened not instantaneously, Keroncong Orchestras Gita Puspita has always been in the process of working and being creative so that he managed to get a place in the hearts of the people of Tegal Regency, especially teenagers. One of the uniqueness of Keroncong Orchestras Gita Puspita is the use of woodwind ensembles for Keroncong music, where this kind of collaboration has never existed before in the Tegal district. This study aims to describe the use of woodwind ensembles in Keroncong music by Keroncong Orchestras Gita Puspita in Tegal. This study uses a qualitative method with a music analysis approach, data collection through observation, interviews, and documentation studies. The results showed that the use of the woodwind ensemble on Keroncong Orchestras Gita Puspita is quite important in composition, because the woodwind ensemble functions as an accent filler, filler, blocking note, and melody note, this is what makes the woodwind ensemble have an important role in every Keroncong Orchestras Gita Puspita arrangement